Competency-Based Education in Three Pilot Programs Examining Implementation and Outcomes - Steele, Jennifer L. (RAND Corporation, 2014)
Competency-based education meets students where they are academically, provides students with opportunities for choice, and awards credit for evidence of learning, not for the time students spend studying a subject. The Bill & Melinda Gates Foundation asked RAND to evaluate three competency-based education grants in terms of implementation, students' experiences, and student performance.